Analysis of miR-1183 Expression Level and Its role in Preeclampsia Pathogenesis via the Regulation of Its Target Gene CHURC1 - Altındirek, Didem; Gümüşoğlu-Acar, Ece; Benian, Ali; Günel, Tuba; Aydınlı, Kılıç (Cerrahpaşa Medical Journal, 2024)
Objective: Preeclampsia (PE) is a multi-systemic disease in pregnancy and a leading cause of maternal and fetal mortality and morbidity worldwide. Elevated expression levels of certain circulating microRNAs (miRs) can be considered potential biomarkers, and have been reported in maternal plasma of pregnant women. We aimed to evaluate the expression profiles of circulating miR-1183 and its putative target mRNA in preeclampsia and their utility for prenatal diagnosis of preeclampsia. Methods: Plasma samples were obtained from pregnant women between 26 and 32 weeks of gestation. Circulating miR-1183 and its target mRNA expression levels were determined by qRT-PCR in maternal plasma of 31 patients with preeclampsia and 22 normotensive pregnancies patient as control. Bioinformatics tools were used to predict the target gene of miR-1183. Results: The expression level of circulating miR-1183 was significantly increased in plasma of preeclampsia patients compared to controls (P = .002). The expression level of CHURC1 gene, the target gene of miR-1183, is dramatically decreased in PE cases compared to controls (P < .001). Spearman’s correlation between miR-1183 and CHURC1 expression levels shows an r-value of −0.37, suggesting a moderate inverse relationship between the 2 parameters but it was not statistically significant (P = .08). By Receiver Operating Curve (ROC) analysis, miR-1183 and CHURC1 showed high accuracy in discriminating PE from controls. The area under the curve (AUC) was found in miR-1183 and CHURC1 at 0.79 (95% CI, 0.62-0.91) and 0.96 (95% CI, 0.78-0.99), respectively. Conclusion: Circulating miR-1183 may be involved in the pathogenesis of preeclampsia via the regulation of its target mRNA, CHURC1. Cite this article as: Altındirek D, Gümüşoğlu-Acar E, Benian A, Günel T, Aydınlı K. Analysis of miR-1183 expression level and its role in preeclampsia pathogenesis via the regulation of its target gene CHURC1. Cerrahpaşa Med J. 2024;48(2):146-151.